THE TEACHER IN INTERWAR SOCIETY: PROFESSIONAL MISSION AND SOCIAL CHALLENGES IN THE TERNOPIL VOIVODESHIP (BASED ON THE MATERIALS OF ECHO NAUCZYCIELSKIE) - Vasylyshyn , Stepan (Young Scholars Grinchenko – Seton International Journal, 2026)
The aim of the study is to conduct a comprehensive analysis of teachers’ professional mission and the socio-economic challenges that shaped their activities in 1921–1939, based on periodical materials, archival sources, and regulatory legal acts. It has been established that the teaching profession in the Ternopil Voivodeship during the interwar period performed functions far broader than those envisaged by the official educational policy of the Second Polish Republic. The teacher served not only as a transmitter of knowledge but also as a key agent of socio-economic stabilization in local communities, combining pedagogical, administrative, and civic roles. Research indicates that chronic underfunding of the education sector, along with the transfer of responsibility for school maintenance to communes, led to the emergence of an informal practice of teachers’ financial participation in supporting the educational process. This situation effectively transformed the social status of the teacher, turning him into a "community resource", which undermined the material well-being of teachers’ families and contributed to professional burnout. Despite these difficult conditions, the teaching profession demonstrated a high level of self-organization and civic activism. The activities of the Society for the Support of Public School Construction indicate that teachers were the driving force behind the modernization of school infrastructure, ensuring the implementation of large-scale construction projects through community mobilization mechanisms. The organization of “Public School Weeks”, cultural and educational events, and the mobilization of financial resources of the population indicate the effectiveness of grassroots initiatives in overcoming the structural limitations of state policy.